TINGKAT KEPUASAN PELANGGAN PENGGUNA TERHADAP JUMLAH KUNJUNGAN JASA PELAYANAN FISIOTERAPI PADA OKTOBER 2009 DI PUKESMAS SE-KABUPATEN SUKOHARJO - MIFTAHURRAHMAH , RIFKA (2009)
Puskesmas is accomplishment unit which a practice operational duties of health development in jurisdiction district. Public choose Puskesmas as if medical treatment because economy consideration and location factor. So that, as if once top of public health care of marginal mass, Puskesmas need to promote physiotherapy service and management of service. Quality of health service correlate with costumer satisfaction. Physiotherapy service in Puskesmas is a product, need to unfolding design quality of physiotherapy service which can to fulfil even if to exceed costumer needs and expectantly, so that can to preserve and increase quantity of visit. The objective of this research is the correlation of costumer satisfaction level and quantity of visit physiotherapy service at October 2009 at Sukoharjo residence's Puskesmas. Research design that is used is descriptive method with survey, number o the sample 263 in divide on 6 cluster. The result of the analysis and statistical parametric correlation test of Pearson Product Moment methods with the help of computer programme SPSS version 13.0. Result of research indicate that there is significant, positively, and strong correlation between costumer satisfaction level and quantity of visit physiotherapy service at October 2009 at Sukoharjo residence's Puskesmas. By calculating the value of r xy > r table (0,607 > 0,148). Puskesmas must be attention about customer needs and elements which can influence customer satisfaction level so then can preserve and increase quantity of visit.